2018
DOI: 10.1111/rode.12403
|View full text |Cite
|
Sign up to set email alerts
|

Female leaders and gender gaps within the firm: Evidence from three Sub‐Saharan African countries

Abstract: We study the association between the gender of the highest-ranking manager (the CEO) and gender differences in employees' outcomes using detailed linked employer-employee data from the formal sector in Cameroon, Côte d'Ivoire, and Senegal. Our empirical strategy relies on the inclusion of firm fixed effects and workers' characteristics. Our results point toward a negative correlation between female CEOs and the relative wages and job satisfaction of female employees. However, female employees working under a f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 34 publications
0
2
0
Order By: Relevance
“…Using matched employee-employer data, Halld en et al (2018) found that the overall wages of female employees are 3% lower when the managers are women. La Mattina et al (2018) also confirmed the existence of the queen bee phenomenon through a study of three sub-Saharan African countries and found that female CEOs would reduce the relative wages of female employees. Therefore, we propose the following competing hypotheses:…”
Section: Theoretical Underpinning and Hypothesesmentioning
confidence: 70%
“…Using matched employee-employer data, Halld en et al (2018) found that the overall wages of female employees are 3% lower when the managers are women. La Mattina et al (2018) also confirmed the existence of the queen bee phenomenon through a study of three sub-Saharan African countries and found that female CEOs would reduce the relative wages of female employees. Therefore, we propose the following competing hypotheses:…”
Section: Theoretical Underpinning and Hypothesesmentioning
confidence: 70%
“…A few studies employ data with samples representative of all industries (namely, Abendroth, Melzer, Kalev, & Tomaskovic‐Devey, ; Cohen & Huffman, ; Hultin & Szulkin, ; LaMattina, Picone, Ahoure, & Kimou, ). However, these studies are subject to other limitations that may limit the generalizability of their findings.…”
Section: Datamentioning
confidence: 99%